PENGARUH UMUR BATANG BAWAH DAN NAUNGAN TERHADAP KEBERHASILAN GRAFTING PADA TANAMAN DURIAN (Durio zibethinus Murr.) LOKAL - Hanif Fatur Rohman; Roedy Soelistyono; Nur Edy Suminarti (BUANA SAINS, 2018)
Durian (Durio zibethinus Murr.) has a great sale value, beside its delicious flavor; it also contains variety of nutrients such as Vitamins B, C, E and Iron that are beneficial for human health.The main problems in improving the local durian is limited availability of quality seeds. Durian development undertaken by local farmers generally from generative, thereby causing the vegetative phase takes longer (about 7-10 years) and make generative phase come later. It is one of the obstacles in the productivity and quality of durian.It is one of the obstacles in the productivity and quality of durian. But with advances in technology, these obstacles can be overcome by using a mini-graft method to produce superior durian seedling.The purposes of this research are to get the right age and precentage of shade on grafted durian seedling and to determine the influence on growth and yield of grafted plants. This research conducted on january – oktober 2016 on Durio Kingdom Farm, Ngantang, Malang Regency on 660 asl. The experiment was conducted using split plot design. The main plot is percentage shade (N): shade 0%, shade 40%, shade 60% and shade 80%, while the subplots are seedlings (A) is 15 weeks age rootstock, 17 weeks age rootstock and 19 weeks age rootstock. The results of this study showed that 17 weeks Age seeds give better results, shade are gives better results for use in plant nurseries durian is shade with a density of 40%.